2018
DOI: 10.1186/s12974-018-1109-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexamethasone on the Li-pilocarpine model of epilepsy: protection against hippocampal inflammation and astrogliosis

Abstract: BackgroundTemporal lobe epilepsy (TLE) is the most common form of partial epilepsy and is accompanied, in one third of cases, by resistance to antiepileptic drugs (AED). Most AED target neuronal activity modulated by ionic channels, and the steroid sensitivity of these channels has supported the use of corticosteroids as adjunctives to AED. Assuming the importance of astrocytes in neuronal activity, we investigated inflammatory and astroglial markers in the hippocampus, a key structure affected in TLE and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 88 publications
(97 reference statements)
1
17
0
Order By: Relevance
“…There is an important therapeutic implication here; evidence of a protective, regenerative response at all post-injury intervals indicates that therapies augmenting these responses may be beneficial regardless of how many months or years have passed since the initial TBI. For instance, since steroid-induced decreases in S100b levels have been shown to reduce inflammation in the hippocampus in a rat model of epilepsy, the significant decrease in expression of S100b at one year post-TBI would protect against inflammation [73]. The increased expression of Atf3 also appears to be a protective response (see Fig 6); a recent study found that neuroinflammation was enhanced in Atf3 knockout mice after TBI [74].…”
Section: Discussionmentioning
confidence: 99%
“…There is an important therapeutic implication here; evidence of a protective, regenerative response at all post-injury intervals indicates that therapies augmenting these responses may be beneficial regardless of how many months or years have passed since the initial TBI. For instance, since steroid-induced decreases in S100b levels have been shown to reduce inflammation in the hippocampus in a rat model of epilepsy, the significant decrease in expression of S100b at one year post-TBI would protect against inflammation [73]. The increased expression of Atf3 also appears to be a protective response (see Fig 6); a recent study found that neuroinflammation was enhanced in Atf3 knockout mice after TBI [74].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on the effects of glucocorticoids in epilepsy and convulsions, but the conclusions are controversial so far [11,12,[28][29][30][31][32][33]. Different dosages, courses, and time points of glucocorticoid administration might be responsible for these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids have proven to be helpful in treatment of epilepsy in numerous clinical and experimental studies [8][9][10][11][12]. Glucocorticoids have two type of receptors in vivo: mineralocorticoid receptors (MRs) of high affinity and glucocorticoid receptors (GRs) of low affinity [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…Epilepsy is a neurological disorder characterized by recurrent and spontaneous seizures caused by excessive, abnormal, and hypersynchronous neuronal discharge [ 106 ]. An imbalance between the excitatory glutamatergic and inhibitory GABAergic neuronal discharges causes brain damage and cell loss [ 107 ]. Astrocytes, a subtype of glial cells, play an important role in regulating cerebral ion homeostasis, transmitter regulation, maintenance of the blood-brain barrier (BBB), and structural, as well as metabolic support of neuronal cells.…”
Section: S100b In Epilepsymentioning
confidence: 99%